Dinamika ketidakpastian pasar keuangan global terhadap stabilitas harga emas sebagai safe haven asset - Sasha Kamila Shaliha; Alfita Zahwarani; Ajeng Faizah Nijma Ilma; Dijan Rahajuni (Journal of Economics Research and Policy Studies, 2025)
The uncertainty in global financial markets led investors to favor safe, stable assets such as gold. Therefore, it was important to explain the factors driving global financial market uncertainty and their impact on gold price stability. This study analyzed the effects of global tensions, exchange rates, and interest rates on the stability of gold prices as a safe-haven asset in Indonesia. The Ordinary Least Squares (OLS) regression method was employed to measure the extent of these effects, and the model was validated using the normality test (Jarque-Bera), autocorrelation test, multicollinearity test, and heteroskedasticity test (White). Monthly data from January 2022 to December 2024 were used in the analysis and were found to be stationary. The study found that exchange rates and interest rates had a positive and significant effect on gold prices, while global tensions had a positive but insignificant effect. These findings were relevant to support investor decision-making and policy formulation, as well as to contribute to the academic literature in international finance.